The safety of the superomedial pedicle for gigantomastia - Chetty, Vaneshri (My University, 2016)
Introduction Breast reduction surgery in women with gigantomastia and macromastia can present as a major challenge to the plastic and reconstructive surgeon. The superomedial pedicle (SMP) technique of breast reduction has been shown to be a safe and efficacious procedure to decrease a moderate size hypertrophy of the mammary glands. A myriad of techniques has been demonstrated to decrease the size of extremely large and hyperplastic breasts, they can, however, potentially result in complications, amongst the most dreaded being damage to the nipple-areola complex (NAC), especially necrosis and loss of sensibility. Excessive breast hypertrophy is termed macromastia or gigantomastia. Macromastia is defined as an excess or hypertrophy of breast tissue over 1.0 kg per breast but less than 2.0 kg. Gigantomastia is defined as hypertrophied breast tissue equal to and greater than 2.0 kg per breast. [1] McKissock recommended breast amputation mammoplasty and free nipple grafts for those reductions that required removal of more than one kilogram of parenchyma, or if the length of vertical distance is greater than 35 cm. [2] Numerous pedicled techniques of breast reduction exist and pedicles can be based in any of the four quadrants as well as centrally. While the 2 main skin excision patterns include the Wise pattern (inverted T-shape closure) and the Vertical pattern. (Diagram.1 & 2) Objective The objective of this study was to determine exactly how efficiently the superomedial pedicle (SMP) technique performs breast reduction surgery, particularly in candidates with extremely large breasts, viz. macromastia and gigantomastia. To evaluate the efficacy and complication rate of the SMP reduction mammoplasty technique, with wise pattern skin closure, for macromastia and gigantomastic breasts, at two different hospitals in Johannesburg, as performed by 2 surgeons, Chetty, V. and Ndobe, E. Methods Retrospective review of patient records with macromastia and gigantomastia who had undergone the SMP technique reduction mammoplasty, over a 4-year period. Complications were assessed at 1 week, 3 weeks, 6 months and a mean of one-year post operatively. Photo records were taken at each stage. Results There were a total of 31 patients, 62 breasts, with macromastia and gigantomastia that had an SMP pattern of reduction. The mean age was 30.1 years, mean BMI was 28.1 and average resection weight from each breast was 1835 g. The mean N-N was 44.13 cm. The majority, 90 % of patients had a good aesthetic outcome with less than 20% having any long-term complications, which were all relatively minor. Conclusion The SMP reduction mammoplasty efficiently reduces extremely large breasts while preserving the integrity of the NAC, sensation and simultaneously provides a wellshaped, projecting breast in macromastia and gigantomastia patients.
A research submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in Plastic and Reconstructive Surgery 18 July 2016 Johannesburg